Penerapan Nilai Integritas dan Anti Korupsi Melalui Proyek Penanaman Pohon di Lingkungan Kampus Sebagai Pengembangan Ide Media Pembelajaran Kreatif di Sekolah Dasar - Fauzia Istiqomah; Muammar Fadhil; Rika Ameliya; Itsna Naila Zulfa; Nazwa Kirani Nasuha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of integrity and anti-corruption values through a tree planting project on campus and examine how this experience can be developed into creative learning media ideas in elementary schools. The background of this research is driven by the increasing cases of corruption in Indonesia as reported by Transparency International and Indonesia Corruption Watch (ICW), so that concrete and meaningful value education needs to be carried out from an early age. This study uses a qualitative descriptive method with an experiential learning approach, which focuses on building understanding and character through direct experience. Data were obtained through observations of plant care activities, analysis of tree development as a result of responsible and disciplined practices, and a review of literature related to integrity education, character education, and anti-corruption values. The results show that tree planting and maintenance activities can bring out integrity values such as honesty, discipline, responsibility, hard work, caring, and independence, which are formed through habits, reflection, and interaction within groups. In addition, the authentic experience in this project can be used as inspiration for the development of creative learning media for elementary school students, for example through mini-projects, plant growth journals, or visual media that emphasize the importance of caring for the environment as a form of anti-corruption behavior. These findings confirm that real-life experiential learning has great potential in instilling the values of integrity and anti-corruption sustainably in students starting from elementary school level.